Cost‐effectiveness Analysis of Follow‐up Strategies for Thunderclap Headache Patients With Negative Noncontrast CT. (13th February 2016) - Malhotra, Ajay; Wu, Xiao; Kalra, Vivek B.; Schindler, Joseph; Forman, Howard P.
Abstract: Objectives: Accurate diagnosis of acute subarachnoid hemorrhage (SAH) is critical in thunderclap headache patients due to high morbidity and mortality associated with missed aneurysmal bleeds. The objective of this study was to determine the utility of computed tomography angiography (CTA) in managing patients with acute, severe headaches and negative noncontrast CT and assess the cost‐effectiveness of three different screening strategies—no follow up, CTA, and lumbar puncture (LP). Methods: A modeling‐based economic evaluation was performed with a time horizon of 1 year for thunderclap headache patients in the emergency department with negative noncontrast CT for SAH. Sensitivity analyses were performed to determine the effect of sensitivity of CT and the prevalence of SAH on cost‐effectiveness. Results: Lumbar puncture follow‐up has the lowest cost and the highest utility in the mathematical model. The Monte Carlo simulation shows noncontrast CT with LP follow‐up to be the most cost‐effective strategy in 85.3% of all cases even at a 1 million/quality‐adjusted life‐years willingness‐to‐pay. Sensitivity analyses demonstrate that LP follow‐up should be performed, except for when CT sensitivity exceeds 99.2% and the SAH prevalence is below 3.2%, where no follow‐up may be considered. Conclusions: Although CTA is frequently used for evaluation of thunderclap headache patients, its utility is not clearly defined. LP follow‐up is shown to be the most cost‐effective strategy for evaluation of thunderclap headache patients in most clinical settings.